(untitled) (Journal of Political Science and International Relationship, 2024)
Vote-selling has detrimental implications for Ghana’s democratic process and principles. The study aimed to examine the implications of vote-selling on Ghana’s democracy. A qualitative approach and case study design were adopted. The convenience sampling technique was used to select 14 participants for the study. Data was analyzed using thematic analysis. The analysis shows that voters sell their votes because of unfulfilled campaign promises, the readiness of politicians to spend on campaigns, and the voters’ willingness to use elections to get their share of the national cake. Vote-selling transactions start with convincing voters, followed by the process of channeling incentives, conveying voters to voting stations, and ending with proof of voting. Also, the findings show, that the inability to select competent leaders, corruption, tyranny, inability to initiate good policies and the inability to hold politicians accountable are the implications of vote-selling on Ghana’s democracy. The study concludes that vote buying and selling are a contract where both politicians and voters, that is sellers and buyers profit while ignoring the aftermath consequences of such an action. The study also concludes that vote-selling has detrimental implications for Ghana’s democracy. We recommend that NGOs, electoral commissions, civil societies, and non-state actors should spearhead and strengthen democracy by mounting vigorous campaigns to educate the electorates not to accept financial or material benefits before they vote for a particular candidate. Moreover, the consequences of vote-selling and buying should be included in high school curricula to educate Ghanaians on its implications